– Effect of applying a teaching strategy based on brain absorption to people with intellectual disabilities– Case Study on Students with Intellectual Disabilities and Charges Syndrome - Almuqary, Mshal Abdullah (Journal of Educational and Psychological Sciences, 2019)
This research examined the impact of hemispheric-teaching strategy on individuals with intellectual disability. The author argues that if one of the two hemispheres is more dysfunctional by presenting poorer attributed functions than the other due to abnormal brain development and one is more functional than the other, processing and analyzing inputs and information would be manifested in the superior hemisphere thus teaching those individuals by which it meets their dominant hemisphere will increase their performance. A sample of two students with Intellectual Disabilities and CHARGE Syndrome underwent right and left-hemispheric teaching strategies and were assessed before and after the intervention to examine the argument. Both participants exhibited improvement in their performance on the assigned task, but more improvement was exhibited from the participant who underwent the left-hemispheric teaching strategy.
Keywords: brain lobes; dominant brain lobe; brain functions; cognitive processes; cognitive neuroscience; teaching strategies